Caracterização fenotípica e molecular de Pseudomonas aeruginosa resistentes a carbapenêmicos e produtoras de Metalobeta- lactamase, isoladas em hemoculturas de crianças e adolescentes com câncer - Fernandes, Thaís Ávila [UNIFESP] (2008)
Pseudomonas aeruginosa is an important opportunist pathogen, particularly for oncologic and neutropenic hospitalized patients. One of the main characterisitic of this bacteria is the development of multiple antibiotic resistance, including the carbapenems. The first metallo-beta-lactamase (MBL) encoding the gene blaSPM-1 reported in the literature was isolated in the year 2000 from a patient admitted to the Instituto de Oncologia Pediatrica (IOP/GRAAC - UNIFESP). Objective: To evalute the prevalence of P. aeruginosa carbapenem resistant and MBL producers isolated from bloodstream samples collected from patients admitted to the IOP in the period 2000- 2005; to describe the dissemination of these enzymes by molecular typing and clinical/epidemiological data. Methods: 56 P. aeruginosa isolates from 49 patients were tested against 10 different antibiotics by disc diffusion. The isolates resistant to carbapenems were tested by disc-approximation method and submitted to PCR reaction for detection of MBLs genes. The isolates producers of blaSPM-1 were molecular typed by PFGE. The clinical and epidemiological data were obtained from the patiens charts. Results: From 2000 to 2005, 32 out of 56 P. aeruginosa isolates were classified as carbepenem reistant by disc diffusion. Eighteen out of 32 (56,2%) isolates carried blaSPM-1 and revealed the same molecular typing profile. We did not detected other MBL blaIMP-1, blaVIM-1 and blaVIM-2. The antibiotic therapy was considered adequate in only 17,7% of the patients with P. aeruginosa bacteremia encoding the gene blaSPM-1. We observed a higher letality rate, in the period of 30 days after bacteremia, in these patients compared with the letality of patients with P. aeruginosa bacteremia resistant to carbapenems but not carring MBL. Conclusion: We detected the presence of a P. aeruginosa clone resistant to carbapenems and carrying the gene blaSPM-1 that persisted in blood stream isolates of patients admitted to the IOP from 2000 to 2005. A high letality rate and inadequacy of initial antibiotic treatment was observed justifying a strict epidemiologic surveillance and re-evalutation of antibiotic treatment protocol.